Acellular pertussis vaccine effectiveness and waning immunity in Alberta, Canada: 2010–2015, a Canadian Immunization Research Network (CIRN) study. Issue 30 (9th July 2019) - Bell, Christopher A.; Russell, Margaret L.; Drews, Steven J.; Simmonds, Kimberley A.; Svenson, Lawrence W.; Schwartz, Kevin L.; Kwong, Jeffrey C.; Mahmud, Salaheddin M.; Crowcroft, Natasha S.
Highlights: Acellular vaccine provides moderate protection in the years following vaccination. Young children who follow the vaccine schedule are well protected from pertussis. The decrease in protection after 5 years is consistent with waning immunity. Abstract: Background: Pertussis is still frequently reported in Canada. In Alberta, pertussis incidence ranged from 1.8 to 20.5 cases per 100, 000 persons for 2004–2015. Most cases occurred in those aged <15 years. In Alberta, acellular formulations replaced whole-cell in 1997. We investigated pertussis vaccine effectiveness (VE) using a test-negative design (TND) study. Methods: We included all persons who had a real-time PCR laboratory test for Bordetella pertussis between January 1, 2010 and August 31, 2015, in the province of Alberta, Canada. Vaccination history was obtained from Alberta's immunization repository. Vaccination status was classified as complete, incomplete, or unvaccinated, based on the province's vaccination schedule. Persons who had received ≥one dose of whole cell vaccine were excluded from analysis. Multivariable logistic regression models were used to estimate adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) for pertussis infection by time since last vaccination. We adjusted for vaccination status, age, sex, neighbourhood income, urban/rural status, and the presence of a co-morbid condition. VE was calculated as [(1 − aOR) * 100]. Results: Of the 12, 149 tests available, 936 (7.7%) were positive for Bordetella pertussis . Among the full cohort, VE was 90% (95% CI 87–92%) at 1 year, 81% (95% CI 77–85%) at 1–3 years, 76% (95% CI 68–82%) at 4–7 years, and 37% (95% CI 11–56%) at 8 or more years since a last dose of acellular pertussis vaccine. Conclusions: Pertussis VE was highest in the first year after vaccination, then declined noticeably as years since a last vaccination increased. Our results suggest that a large number of adolescents and adults are susceptible to infection with Bordetella pertussis . Regular boosters throughout childhood, adolescence, and during pregnancy may be needed.